Gene therapy for the eye focus on mutation-independent approaches. Issue 1 (February 2015) - Dalkara, Deniz; Duebel, Jens; Sahel, José-Alain
<x xml:space="preserve">Abstract</x> Purpose of review This review will discuss retinal gene therapy strategies with a focus on mutation-independent approaches to treat a large number of patients without knowledge of the mutant gene. These approaches rely on the secretion of neurotrophic factors to slow down retinal degeneration and the use of optogenetics to restore vision in late-stage disease. Recent findings Success in clinical application of adeno-associated virus (AAV)-mediated gene therapy for Leber's congenital amaurosis established the feasibility of retinal gene therapy. More clinical trials are currently on their way for recessive diseases with known mutations. However, the genetic and mechanistic diversity of the retinal diseases presents an enormous obstacle for the development of gene therapies tailored to each patient-specific mutation. To extend gene therapy's promise to a large number of patients, evidence suggests retina-specific trophic factors, such as rod-derived cone viability factor, can be used to slow down loss of cone cells responsible for our high acuity vision. In parallel, it has been shown that microbial opsins are able to restore light sensitivity when expressed in blind retinas. Summary Recent findings imply that using the viral technology that has been demonstrated as well tolerated in patients, there are opportunities to develop widely applicable gene therapeutic interventions in clinical ophthalmology.